Pencegahan Penyakit Covid-19 Melalui ‘Amalan Mencuci Tangan’ Daripada Perspektif Hadith - Norhasnira binti Ibrahim; Fathima Begum Syed Mohideen (USIM Press, 2024)
The spread of the COVID-19 outbreak in Malaysia in early 2020 has brought a major change in our lives. The community needs to accept that this pandemic is likely to continue until the vaccine and specific treatment like antivirals are identified except if there is a change in attitudes. Scientists are working hard to produce vaccines and antivirals. However, these efforts require ongoing researches. Therefore, in order to prevent this outbreak from spreading continuously within the community, the Ministry of Health (MOH) has outlined three new norms that need to be practised as daily routines, which are frequent hand washing, social distancing, and use of face mask. This is because the chain of infection has to be ended by preventing the transmission of Coronavirus that causes the COVID-19 infection from individuals who are infected to other individuals in a community. Therefore, this paper discusses hand wash practices as a means of preventing COVID-19 disease from the hadith perspective. The two objectives of this study are to study the prevention of diseases through the practice of handwash based on the hadith of the prophet and analyze the relationship between the ' 7 steps of proper hand wash ' with the Hadith in relation to this practice. Qualitative Method has been used in this research and data collection was obtained from the books of Hadith, other books, journal articles, and websites related to the title of the study. The result of the study found that the hand wash practices recommended by the MOH are in line with the recommendations from the Holy Quran and Hadith. In fact, there are a number of hadith that organizes a more complete, detailed, and comprehensive hand wash practice, that involves the hygiene care from the fingertips to the end of the elbow that is easily practised.